Internalizing Character Values through Islamic Religious Education: A Holistic Approach toward Sustainable Quality Education - Rifaldi Wiranata; Ely Surayya; Rauf Adeola Lateef (Profetika: Jurnal Studi Islam, 2026)
Objective: Analyze a holistic approach to internalizing character values in IRE students and formulate a madrass-based integrative model that supports SDG 4. Focus on conceptualization, implementation, the role of teachers, and their impact on student behavior. Theoretical framework: Based on Islamic character education theory, a holistic approach, and a continuous education paradigm. Internalization of values is understood as a pedagogical, cultural, and spiritual process that is integrated in the madrasah ecosystem. Literature review:  The literature emphasizes the importance of integrating curriculum, teacher examples, and school culture in character education. The holistic approach is considered effective in building the affective and spiritual dimensions of students in a sustainable manner. Methods: Using a qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation, and analyzed with Miles, Huberman, and Saldaña interactive models and triangulation. Results: A holistic approach is implemented through the integration of the IRE curriculum, teacher example, religious habituation, strengthening madrasah culture, and social activities that form a sustainable moral ecosystem. IRE teachers act as exemplary agents as well as spiritual companions. This approach has a significant impact on improving students' discipline, religiosity, responsibility, and social concern. Implications: To make a practical contribution to the sustainable development of madrasah character education. Theoretically, it strengthens the integration of Islamic education and the global quality education agenda. Novelty: Offers an integrative conceptual model that systematically blends pedagogic, cultural, and spiritual dimensions. This model enriches the development of madrass-based character education within the framework of sustainability.